2016
DOI: 10.1108/jarhe-05-2014-0054
|View full text |Cite
|
Sign up to set email alerts
|

Absenteeism and performance in a quantitative module A quantile regression analysis

Abstract: Purpose – There is growing evidence that learning is faster, measurably better and more productive in a classroom setting when a student attends classes regularly. Each student brings in his/her experience, skills, and unique learning styles to a class – thus a classroom environment can potentially create positive externalities through which a student can gain substantially from various strengths of his/her peers. However, students do remain absent from their classes for a variety of reasons. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 40 publications
1
11
0
1
Order By: Relevance
“…Modul sangat bermanfaat bagi mahasiswa dengan pencapaian kinerja yang rendah, modul disusun dengan menerapkan pola langkah dan strategi pengajaran agar kinerja mahasiswa rendah dapat meningkat lebih baik untuk berkinerja tinggi. Partisipasi di kelas memiliki dampak positif terhadap kinerja, partisipasi yang berbeda antar mahasiswa memberikan dampak pada kinerja yang berbeda antar mahasiswa, dosen diharapkan memotivasi mahasiswa untuk meningkatkan kehadiran dalam kelas, menyusun modul meningkatkan keterlibatan siswa sehingga mahasiswa lebih proaktif dan antusian dalam kelas serta prestasi akademik meningkat (Pani and Kishore 2016) Modul transformasi geometri sangat dibutuhkan mahasiswa dalam mempelajari geseran, setengah putaran, pencerminan, putaran, pencerminan geser, dan komposisi dua transformasi, dengan adanya modul, diharapkan motivasi mahasiswa untuk belajar mandiri akan meningkat, dan kemampuan berfikir mahasiswa akan semakin baik. (Kirby 2007, Bridge, Hegarty et al 2010, Tiernan 2016) menyebutkan bahwa dampak dari modul adalah meningkatkan mahasiswa untuk berfikir dan bertindak secara kreatif dan inovatif dalam segala hal, modul kewirausahaan disusun dengan pendekatan berbeda, teori, studi kasus, diskusi, aktivitas berbasis pengalaman, dan mahasiswa diberikan tugas dengan tujuan untuk meningkatkan kemampuan mahasiswa calon pendidik dalam berfikir kreatif, mampu memecahkan masalah, dan mempresentasikan gagasan baru.…”
Section: Pendahuluanunclassified
“…Modul sangat bermanfaat bagi mahasiswa dengan pencapaian kinerja yang rendah, modul disusun dengan menerapkan pola langkah dan strategi pengajaran agar kinerja mahasiswa rendah dapat meningkat lebih baik untuk berkinerja tinggi. Partisipasi di kelas memiliki dampak positif terhadap kinerja, partisipasi yang berbeda antar mahasiswa memberikan dampak pada kinerja yang berbeda antar mahasiswa, dosen diharapkan memotivasi mahasiswa untuk meningkatkan kehadiran dalam kelas, menyusun modul meningkatkan keterlibatan siswa sehingga mahasiswa lebih proaktif dan antusian dalam kelas serta prestasi akademik meningkat (Pani and Kishore 2016) Modul transformasi geometri sangat dibutuhkan mahasiswa dalam mempelajari geseran, setengah putaran, pencerminan, putaran, pencerminan geser, dan komposisi dua transformasi, dengan adanya modul, diharapkan motivasi mahasiswa untuk belajar mandiri akan meningkat, dan kemampuan berfikir mahasiswa akan semakin baik. (Kirby 2007, Bridge, Hegarty et al 2010, Tiernan 2016) menyebutkan bahwa dampak dari modul adalah meningkatkan mahasiswa untuk berfikir dan bertindak secara kreatif dan inovatif dalam segala hal, modul kewirausahaan disusun dengan pendekatan berbeda, teori, studi kasus, diskusi, aktivitas berbasis pengalaman, dan mahasiswa diberikan tugas dengan tujuan untuk meningkatkan kemampuan mahasiswa calon pendidik dalam berfikir kreatif, mampu memecahkan masalah, dan mempresentasikan gagasan baru.…”
Section: Pendahuluanunclassified
“…3. Previous performance of students: Previous performance was based on the average overall marks scored in all courses in the previous year (Pani and Kishore, 2016). For level-two and level-three students, previous performance reflected overall performance in the first year and second-year courses respectively; for level-one students, we compiled the previous year's performance data from their high school qualifications.…”
Section: Description Of Datamentioning
confidence: 99%
“…All the studies showed that attendance positively impacted student performance. We follow techniques from Caviglia-Harris (2006) and Pani and Kishore (2016) in our study. The former recognises the possible endogeneity of attendance, which we also do in our exercises; the latter use quantile regression to evaluate the performance of students over the entire range of distribution.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Attendance in HE has received attention in the literature particularly in relation to the impact of attendance at class on academic performance. Most of the studies across disciplines and countries point to some form of relationship between student attendance and achievements (Pani and Kishore 2016;Louis et al 2016;Arulampalam, Naylor, and Smith 2012;Burd and Hodgson 2006;Newman-Ford et al 2008). Nonetheless, critical voices claim that attendance is related to performance in complex ways that need to be unpacked and explored in more depth.…”
Section: The Study Of Attendancementioning
confidence: 99%